Produtividade e composição química de forragem de amendoim forrageiro e trevo vermelho consorciados com gramíneas - Azevedo Junior, Ricardo Lima de (2011)
The objective of this research was to evaluate tree pasture-based systems (PS) with elephant grass (EG) + spontaneous growing species (SGS), ryegrass (RG), for PS1; EG + SGS + forage peanut, for PS2; and EG + SGS + RG + red clover, for PS3. EG was planted 4 m spaced rows. In the cool-season, ryegrass was sowed between rows of EG; red clover was sowed and the forage peanut was preserved in respectively PS. Experimental design was completely randomized with tree treatments (SF), two replicates (paddocks) in completely split-plot time (grazing cycles). Holstein cows receiving 5.5 kg-daily and a complementary concentrate feed were used in the evaluation. The herbage mass parameters, botanical composition, forage production and stocking rate were evaluated. Samples were collected by the hand-plucking method to analyze the organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and organic matter in situ digestibility (OMISD) of pasture; phenols and tannins on legumes. Nine grazing cycle were performed during the experimental period (341 days). The mean values of forage production, stocking rate, crude protein and digestibility were 17.14; 16.80; and 19.47 t/ha; 3.28; 3.34; and 3.60 UA/ha; 13.86; 15.39; and 14.78%; 78.33; 79.23; and 79.94% on the respective PS. SGS increased significantly (P≤0,05) relation to the PS without forage legume. Similar results were observed for forage production OM an NDF in comparison to PS. Nutritive value was similar between forage legumes. Differences (P≤0,05) on condensed tannin tenors were observed between forage legumes. Considering the forage production, stocking rate and nutritive value, the PS mixed to forage legumes showed better performance.